2006
DOI: 10.1196/annals.1374.128
|View full text |Cite
|
Sign up to set email alerts
|

Human Coxiella burnetii Infections in Regions of Bosnia and Herzegovina, 2002

Abstract: Acute infections in humans and animals caused by Coxiella burnetii (C. burnetii) are becoming an important medical problem for Bosnia and Herzegovina (B&H). From a clinical and epidemiological aspect, Q fever represents a complex medical problem, considering that one of the highest incidence rates of Q fever in Europe has been recorded during the last few years in B&H. The first case of this disease in B&H was described in 1950, by Muray et al., and the first epidemic, with 16 infected individuals, was recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Seroprevalence analysis in Italy indicated that the C. burnetii distribution in sheep and goats is very high (38% and 47% respectively). A considerable number of Q-fever outbreaks have been observed in Bosnia and Herzegovina, where sheep and goats have been shown to be the source of infection in humans [5].…”
Section: Discussionmentioning
confidence: 99%
“…Seroprevalence analysis in Italy indicated that the C. burnetii distribution in sheep and goats is very high (38% and 47% respectively). A considerable number of Q-fever outbreaks have been observed in Bosnia and Herzegovina, where sheep and goats have been shown to be the source of infection in humans [5].…”
Section: Discussionmentioning
confidence: 99%
“…In other regions of the world, sheep seroprevalence ranges from 16.5% to 80% [ 37 ]. An outbreak of Q fever in Netherlands and an outbreak in Bosnia-Herzegovina showed that sheep, along with goats, are the main source of infection for humans [ [38] , [39] , [40] ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, its prevalence in both humans and animals has increased significantly in Europe [1]–[7]. In particular, the epidemic in the Netherlands in 2009 left almost 4,000 patients diagnosed with this disease, has highlighted the demand for improved more selective tools for its diagnosis and for the typing of C. burnetii , based on methods that have high levels of inter-laboratory reproducibility and that can be performed at non-specialized laboratories (Fig.…”
Section: Introductionmentioning
confidence: 99%